Perfectionism, pre-competitive worry, and optimism in high-performance youth athletes - Dunn, J. G.; Gotwals, J. K.; Dunn, J. C.; Lizmore, M. R. (International Journal of Sport and Exercise Psychology, 2020)
Different aspects of perfectionism have been associated with an array of adaptive and maladaptive cognitive, affective, and behavioural correlates in sport. However, relatively little is known about the links between athletes` perfectionistic tendencies and their state-level thoughts and expectancies (i.e. mindset) in the lead up to competition. The purpose of this study was to explore relationships between perfectionistic strivings, perfectionistic concerns, and the future-oriented thoughts (i.e. worries) and expectancies (i.e. optimism) of athletes as they prepared to compete. A sample of 144 male youth high-performance Canadian football players (M age = 16.41 years, SD = 1.48) completed domain-specific measures of perfectionism, pre-competitive worry, and optimism 24 h prior to the start of an important competition. Canonical correlation (R C) analysis produced two interpretable canonical functions. In the first canonical function, a canonical variate resembling a maladaptive profile of perfectionism (i.e. high strivings combined with high concerns) was positively correlated (R C1 = .66) with a canonical variate consisting of high worry and low optimism. In the second canonical function, a canonical variate resembling an adaptive profile of perfectionism (i.e. high strivings combined with low concerns) was positively correlated (R C2 = .48) with a canonical variate consisting of low worry and high optimism. The results highlight the importance of treating perfectionism as a multidimensional construct and indicate that the pre-competitive mindset of athletes (as reflected by the degree to which athletes worry and feel optimistic) appears to be associated with athletes` perfectionistic orientations in sport.